Philosophical Synthesis of Basic Education: Thoughts of Pioneering Figures of the Indonesian Nation: Sintetis Filosofis Pendidikan Dasar: Pemikiran Tokoh Perintis Bangsa Indonesia - Vanda Rezania; Nurul Aini; Wahono Widodo; Hendratno Hendratno (Universitas Muhammadiyah Sidoarjo, 2026)
Modern Indonesian education is rooted in the philosophical thought of the nation’s founding figures. Through a comparative-philosophical analysis of the ideas of Ki Hadjar Dewantara, KH. Ahmad Dahlan, KH. Hasyim Asy’ari, and R.A. Kartini, this study aims to formulate a solid and relevant philosophical foundation for basic education. The results of the study show that Indonesia’s educational philosophy is a synthesis of four complementary dimensions cultural humanism, spirituality and character, modernity and progress, and foundational emancipation that converge toward a single goal: to produce students who are religious and of good moral character, independent and critical thinkers, and adaptable to the times without losing their cultural roots. In digital curricula, this synthesis calls for a transformation of the teacher’s role into that of a Pamong (guide to independence), a Murobbi (instiller of good manners), an Innovator (integrator of science and religious values), and an Emancipator (promoter of family collaboration and gender equality). These findings confirm that the ideas of these four figures are not merely a historical legacy, but rather an operational philosophical framework that can serve as a direct reference for curriculum policy formulation and the development of elementary school teachers’ competencies in the digital age. Highlights: Cultural humanism, spirituality, modernity, and emancipation converge into one model. Teachers assume Pamong, Murobbi, Innovator, and Emancipator roles. Classroom literacy combines autonomy, ethics, science, equality, and family participation. Keywords: Indonesian Education Philosophy, Primary Education, Digital Literacy, Teacher Roles, Curriculum Policy